Marketing Research Challenges and Opportunities - Dawn Iacobucci (Revista Brasileira de Marketing, 2018)
This article considers three contemporary challenges faced by today’s marketing researchers. These challenges involve big data, survey data, and publishing. With a marketer’s perennial optimism, each challenge is seen as an opportunity, to obtain better information than ever before. Received on: 06/29/2018 Approved on: 08/30/2018 Responsible Editors: Prof. Dr. Marcelo Luiz Dias da Silva Gabriel Prof. Dr. Dirceu da Silva Evaluation Process: Guest Paper Introduction